Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.24036/ekj.v4.i1.a333
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Aplikasi Media Pembelajaran Berbasis Android pada Materi Larutan Elektrolit dan Nonelektrolit

Abstract: The purpose of this study is to develop the Melonit applications an Android-based learning media on electrolyte and non-electrolyte solutions, and disclose the level of validity of the developed product regarding the validity of the content, construct and media. This type of research is Educational Design Research applying the Plomp development model, which consists of three stages, namely preliminary research, prototyping stage and assessment stage. The research instruments used were in the form of content va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Teachers have never used android-based learning media applications in their lessons. Some literature states that android-based learning media applications have been developed on electrolyte and non-electrolyte solutions, thermochemistry, basic laws of chemistry, atomic structure, periodic system, and chemical equilibrium [6,7,8,9,10,11]. It is concluded that the android-based learning media application is valid for learning.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers have never used android-based learning media applications in their lessons. Some literature states that android-based learning media applications have been developed on electrolyte and non-electrolyte solutions, thermochemistry, basic laws of chemistry, atomic structure, periodic system, and chemical equilibrium [6,7,8,9,10,11]. It is concluded that the android-based learning media application is valid for learning.…”
Section: Introductionmentioning
confidence: 99%
“…One of the abstract chemical materials is salt hydrolysis material. Abstract chemical concepts will be easier to understand by involving three levels of chemical representations, namely macroscopic, submicroscopic and symbolic representations (Sagita et al, 2018), (Yani et al, 2019), (Rachmawati et al, 2021), (Utari & Azra, 2022), (Adawiyah & Azra, 2022). Learning by applying chemical multirepresentations provides facilities for meaningful or in-depth learning to occur (Sagita et al, 2017), and is able to improve understanding of chemical concepts and chemical problem solving (Sari & Helsy, 2018).…”
Section: ▪ Introductionmentioning
confidence: 99%